A Proposal for Classroom Lessons on Information Security with a View to Junior and High School Collaboration - Yamamoto, Shu; Yoshida, Takuya (Computer & Education, 2023)
In this study，we proposed a class incorporating new teaching materials and practical training on information security in the junior high school "Technology" course ，with an awareness of the collaboration between the junior high school and high school. The trial lessons were given to 204 first-year junior high school students，and a questionnaire survey was conducted before and after the class to verify its usefulness. In the trial lessons，we selected a subject that was familiar and interesting to the students，and conducted hands-on activities using visual experience tools. As a result，the mean scores of "knowledge and skills，" "thinking，judgment，and expression，" and " proactive attitude toward learning" increased significantly.